2005
DOI: 10.1111/j.1742-4658.2005.04892.x
|View full text |Cite
|
Sign up to set email alerts
|

Homoadenosylcobalamins as probes for exploring the active sites of coenzyme B12‐dependent diol dehydratase and ethanolamine ammonia‐lyase

Abstract: AdoCbl participates as coenzyme for the enzymes that catalyze carbon skeleton rearrangements, heteroatom eliminations, and intramolecular amino group migrations [1][2][3]. For example, diol dehydratase (EC 4.2.1.28) and ethanolamine ammonia-lyase (EC 4.3.1.7) catalyze the dehydration of 1,2-diols and the deamination of ethanolamine to the corresponding aldehydes, respectively [4][5][6]. These reactions proceed by a radical mechanism, and an essential early event in all the AdoCbl-dependent rearrangements is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 53 publications
(85 reference statements)
1
19
2
Order By: Relevance
“…Among the cobamides we tested, the maximum differences in Sm MCM turnover were 3-fold. We did not observe inhibition of MCM activity with any cobamides, in contrast to the strong inhibition that has been observed with analogs containing variations in the upper ligand or central metal, known as antivitamins (111113).…”
Section: Discussioncontrasting
confidence: 99%
“…Among the cobamides we tested, the maximum differences in Sm MCM turnover were 3-fold. We did not observe inhibition of MCM activity with any cobamides, in contrast to the strong inhibition that has been observed with analogs containing variations in the upper ligand or central metal, known as antivitamins (111113).…”
Section: Discussioncontrasting
confidence: 99%
“…Among the cobamides we tested, the maximum differences in SmMCM turnover were 3-fold. We did not observe inhibition of MCM activity with any cobamides, in contrast to the strong inhibition that has been observed with analogs containing variations in the upper ligand or central metal, known as antivitamins (Calafat et al, 1995;Fukuoka et al, 2005;Widner et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…The observed small activity of AdoMeCbl as cofactor of DD and EAL, that is, 0.27 % and 0.13 % that of AdoCbl for DD and EAL, respectively, [15] has been a puzzle that induced us to undertake the present crystallographic study. It is highly improbable that these residual activities are caused by AdoCbl as an impurity.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, these homologues of coenzyme B 12 also seem to be useful probes for exploring the active sites of AdoCbl‐dependent enzymes. Spectroscopic studies indicated that these analogues do not undergo significant Co−C bond cleavage upon binding to apoenzymes within at least 10 min [6a,15] …”
Section: Introductionmentioning
confidence: 99%